2019
DOI: 10.1002/app.48333
|View full text |Cite
|
Sign up to set email alerts
|

Near‐visible stereolithography of a low shrinkage cationic/free‐radical photopolymer blend and its nanocomposite

Abstract: In this work, a newly prepared cationic/free-radical photopolymer, which consists of two epoxies and a tetrafunctional acrylate, is presented for the first time for a visible light stereolithography (SL), showing the advantages of both cationic and free-radical resins. An onium salt, commonly used as a cationic UV initiator, and a photosensitizer make the blend suitable for a near-visible (405 nm) SL. An increase in the polymerization rate and a drop in the induction period are observed for the newly prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…A potential explanation can be found in the loss of structural integrity observed in the 3D printed 12 BP over time ( Figure 10 ). The clear resin photopolymer used to manufacture the 3D printed 12 BP suffers, in fact, from significant limitations in terms of mechanical properties and tends to deform over time and light exposure [ 41 , 42 , 43 ]. Even a minimal change in the BP geometry could eventually result in a print with poor dimension accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…A potential explanation can be found in the loss of structural integrity observed in the 3D printed 12 BP over time ( Figure 10 ). The clear resin photopolymer used to manufacture the 3D printed 12 BP suffers, in fact, from significant limitations in terms of mechanical properties and tends to deform over time and light exposure [ 41 , 42 , 43 ]. Even a minimal change in the BP geometry could eventually result in a print with poor dimension accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…The printed meniscus showed enhanced mechanical properties and was found a promising replacement for the native meniscus tear problem. Invernizzi et al [ 134 ] fabricated cationic radical free photopolymer using silica nanoparticles using stereolithography. It was observed that the nanoparticles provided a reinforcing and toughening effect to the photopolymer.…”
Section: Additive Manufacturing Using Polymersmentioning
confidence: 99%
“…Suriano et al investigated a modern SLA resin system, based on the combination of cycloaliphatic epoxy resins and acrylic monomers [ 46 ]. They reported a reinforcing and toughening effect from the silica nanoparticles.…”
Section: Improving Epoxy Resin Applications With Silica Nanoparticmentioning
confidence: 99%